Model of quality public service system implementation and innovation in the field of government administration in Indonesia - Rifai, Rifai; Adilansyah, Adilansyah (Trigin Publisher, 2024)
Societal demand for qualified and innovative public service has increased. In the era of decentralization, the ability to overcome various public service problems greatly determines the government's credibility. Thus, a capable government would gain more and more support from the people to provide satisfying public service. The quality of service should become all parties' concern within the government, either at the implementation or leadership level, by its role. The regional government needs integrated management within its administration, particularly in licensing services. The service would highly depend on three aspects: the implementation pattern, human resources support, organization, and facilities infrastructure. Therefore, the task force's order, mechanism, and implementation procedures are needed to improve the service.